UCA1 executes an oncogenic role in pancreatic cancer by regulating miR-582-5p/BRCC3 - Hu, Xiaole; Wu, Jiahao; Xu, Jianwei (Frontiers in Oncology, 2023)
Background As a fatal disease, the mechanism of pancreatic cancer is unclear. Urothelial carcinoma antigen 1(UCA1), a long noncoding RNA (lncRNA) that was first reported in bladder cancer, acts as an oncogene. However, the regulatory role and mechanism of UCA1 in pancreatic cancer remain unknown. This study aims to investigate the expression level and prognostic value of UCA1 in pancreatic cancer tissues, the effects and mechanism of UCA1 in regulating cell proliferation, apoptosis and metastasis. Methods UCA1 expression levels in tissues were detected by in situ hybridization (ISH) and the prognostic value was evaluated by univariate and multivariate survival analysis. For in vitro experiments, proliferation was evaluated by a cell count kit assay, Edu experiments, and a clone formation assay. Apoptosis was evaluated by fluorescence-activated cell sorting flow-cytometry. Cell migration and invasion capacities were detected by wound healing and transwell assays. Western blots were performed to detect apoptotic associated molecules and epithelial-mesenchymal transition (EMT) markers. For the in vivo experiment, subcutaneous transplantation models of pancreatic cancer in nude mice were established to observe the tumor growth. The regulatory mechanism of UCA1 was explored by proteomics, bioinformatic analysis, luciferase reporter assays, and rescue experiments. Results ISH staining revealed that UCA1 levels between cancer tissues (n=94) and tumor-adjacent tissues (n=73) did not show significant differences. Survival analysis indicated that high expression of UCA1 was an unfavorable prognosis factor for pancreatic cancer. Downregulation of UCA1 by siRNA significantly inhibited cell proliferation, decreased the capacities of cell migration and invasion, induced cell apoptosis, and inhibited EMT. Furthermore, we demonstrated that UCA1 positively regulated the expression of BRCC3 by inhibiting miR-582-5p. Rescue experiments indicated that either inhibiting the expression of miR-582-5p or enhancing expression of BRCC3 could partly attenuate the antitumor effects of downregulation of UCA1. Conclusion UCA1 acted as an oncogene in pancreatic cancer by partly regulating miR-582-5p/BRCC3, which could be a new therapeutic target for pancreatic cancer.